HUBUNGAN PENGENDALIAN DIABETES MELLITUS DENGAN KUALITAS HIDUP PASIEN DIABETES MELLITUS TIPE 2 - Lestari, Nita Yulidia; Safri, Safri; Zulfitri, Reni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Type 2 Diabetes Mellitus is a diabetes group with the highest prevalence that can be controlled by four pillars of diabetes mellitus control. The purpose of this research is to know the relationship between control of diabetes mellitus and the quality of life of patients with type 2 diabetes mellitus in the worked area of Rejosari Pekanbaru Health Center. The research design by used descriptive correlation with cross sectional approach. The sample of this research were 77 respondents which taken by used non-probability sampling with a type of purposive sampling. The measuring instrument used is the diabetes mellitus control questionnaire and the World Health Organization Quality Of LifeBREF (WHOQOL-BREF) questionnaire. The results of this research used by Chi Square test showed that there was a correlation between education and quality of life (p value = 0,017), there was a correlation between nutritional therapy and quality of life (p value = 0,032), there was a correlation between physical exercise and quality of life (p value = 0,003), and there wasn’t a correlation between pharmacological therapy and quality of life (p value = 0,156). The conclusion of this research, there were a correlation between education, diet, dan physical exercise with quality of life. However, there wasn’t correlation between pharmacological therapy with quality of life. Keywords: diabetes mellitus, quality of life, WHOQOL-BREF